PENGARUH KEPUASAN PELANGGAN, INOVASI PRODUK DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN EMINA DI KOTA SOLO - ANITA NADIA AMBARSARI (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2020)
This study aims to determine the effect of customer satisfaction, product innovation and brand image on Emina customer loyalty in Solo city. The subjects of this study were 97 respondents who were Emina users. Data collection methods to determine the effect of customer satisfaction, product innovation and customer loyalty using a questionnaire. The results of this study indicate that customer satisfaction, product innovation, and brand image simultaneously and significantly influence customer loyalty for Emina products. Customer satisfaction partially has a positive and significant effect on customer loyalty of Emina products. Product innovation does not have a positive and significant effect on customer loyalty of Emina products. Brand image has a positive and significant effect on customer loyalty of Emina products.